New Records of Plants from Andaman and Nicobar Islands-I - Balakrishnan, N. P.; Nair, N. G. (Indian Forester, 1977)
Seven plants are reported as new records for the Aadaman and Nicobar Islands, of which Uvaria rufa Bl., Aerchynanthus griffithii R. Br., and Phyllanthus gomphocarpus Hook. f., are new records for India.